Age and serum anti-Müllerian hormone levels as predictors of time to return of menses after chemotherapy - Madhavi-Priya Singh; Rashi Kalra; Franca Agresta; Alec Leos; Samith Minu Alwis; Alex Polyakov; Genia Rozen; Kate Stern (Reproduction and Fertility)
Chemotherapeutic agents result in the loss of growing follicles, which can manifest as amenorrhoea. Alkylating chemotherapy (AC) is known to be more gonadotoxic than non-alkylating chemotherapy (NAC). Anti-Müllerian hormone (AMH), an indirect marker of ovarian reserve, and age have been investigated as predictors of ovarian function after chemotherapy; however, little is known about the time to return of menses. This study aimed to assess how patient age and baseline serum AMH levels at cancer diagnosis affect the time to return of menses post-chemotherapy. This retrospective cohort study examined oncology patients (n = 67) who underwent chemotherapy and were treated through the Reproductive Services Unit of two institutions in Melbourne, Australia. Primary outcomes included the correlation between age and baseline AMH with time to return of menses after chemotherapy. Secondary outcomes include the change in AMH levels at 6- and 12-months post-completion of chemotherapy. Pairwise correlation of the pre-chemotherapy AMH level and time to return of menses demonstrated statistical significance (Spearman’s coefficient, ρ = −0.40) for patients who underwent AC. This analysis in breast cancer patients who underwent AC displayed a negative correlation but was not statistically significant. No association was found between age and time to return of menses for all cancer (NAC or AC) or breast cancer patients who underwent AC. Higher AMH levels prior to AC were associated with an earlier return of menses after chemotherapy. Age at the commencement of chemotherapy was not associated with return of menses. Further prospective research is required to assess post-chemotherapy recovery of AMH.